Koncepcja wyceny opcji rzeczywistych metodą symulacji Monte Carlo - Wiśniewski, Tomasz (Concept of Monte Carlo Simulation in Real Options Valuation, 2006)
The paper presents the concept of real option valuation based on Monte Carlo simulation of two scenarios: one without option and one with option execution. The difference in expected values of these scenarios amounts to the value of real option. Advantages and drawbacks of real options valuation concept based on Monte Carlo simulation are analysed.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1109, s. 694-703